Direct Oral Anticoagulants vs. Warfarin in Hemodialysis Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis - Elfar, Sohil; Elzeiny, Sara Mohamed; Ismail, Hesham; Makkeyah, Yahya; Ibrahim, Mokhtar (Frontiers in Cardiovascular Medicine, 2022)
Abstract 2) Background The use of Direct Oral Anticoagulants (DOACs) in patients who have both atrial fibrillation (AF) and end-stage renal disease (ESRD) requiring hemodialysis remains controversial, with warfarin remaining the mainstay of the treatment. As hemodialysis patients were excluded from most clinical DOACs trials, the evidence of their efficacy and safety is lacking in this cohort of patients. 3) Aim To review the current evidence investigating safety profile and the efficacy of DOACs in comparison with warfarin in patients with AF and end-stage renal disease (ESRD) requiring hemodialysis. 4) Methods and results We included five studies with a total of 34,516 patients in our meta-analysis. The outcomes were major bleeding, ischemic stroke, systemic embolization, hemorrhagic stroke, gastrointestinal bleeding, minor bleeding, and death. Of these patients, 31,472 (92.14%) received warfarin and 3,044 patients received DOACs (8.91%). No significant differences in the incidence of hemorrhagic stroke, major bleeding, hemodialysis access site bleeding, ischemic stroke, and GI bleeding were found between DOACs and warfarin. However, there were higher rates of systemic embolization, minor bleeding, and death events in patients who received DOACs than in the warfarin group (3.39% vs. 1.97%, P-value = 0.02), (6.78% vs. 2.2%, P-value 0.02), and (11.38% vs. 5.12%, P-value < 0.006) respectively. 5) Conclusion In patients on dialysis who require anticoagulation for AF, warfarin could be associated with a significant reduction in minor bleeding, systemic embolization, and death compared to DOACs. These findings need to be validated by further prospective studies to address the best strategy to deal with the increased thrombotic and bleeding risks in such patients